Development of optimized triaxially electrospun titania nanofiber‐in‐nanotube core‐shell structure. Issue 24 (10th February 2021) - Khan, Muhammad Amir; Ahmad, Adnan; Arshad, Salman Noshear; Nazir, Ahsan; Ahmad, Sheraz; Khan, Muhammad Qamar; Shahzad, Amir; Satti, Aamir Naseem; Qadir, Muhammad Bilal; Khaliq, Zubair
Abstract: One dimensional (1D) nanostructures and its derivatives can be manipulated to serve special functions like hollow structure, and higher surface area. 1D TiO2 nanotube‐in‐nanofibers (NF@NT) are developed through triaxial electrospinning followed by a calcination process. A blended solution of polyvinyl pyrrolidone and tetra ‐butyl titanate is used in outer and inner layers of nanofibers, respectively, while paraffin oil is used in the middle layer. The optimized triaxial nanofibers of 669.4 ± 52.43 nm are developed at 7.5 w/w% concentration, 28 kV applied voltage, and 24 cm spinning distance. TiO2 NF@NT structure is obtained through calcination of optimized triaxial nanofibers at 550°C. Subsequently, the morphology of TiO2 NF@NT and its uniform diameter distribution is confirmed through scanning electron microscopy. Fourier‐transform infrared spectroscopy results indicates the formation of TiO2 NF@NT. X‐Rays diffraction pattern peaks also reveals the presence of both anatase and rutile crystalline phases. The presence of only titanium (Ti) and oxygen (O) elements in the TiO2 NF@NT is confirmed through energy dispersive X‐ray spectroscopy. Brunauer–Emmett–Teller analysis indicates that TiO2 NF@NT has a higher specific surface area of 141.68 m 2 /g compared with the solid TiO2 nanofiber ( 75.31 m 2 /g). This study can be adopted to develop TiO2 NF@NT for wide range of application. Abstract : Triaxially electrospun nanofiber‐in‐nanotube TiO2 structure is developed. COMSOL is used to optimize the electric field intensity to develop TiO2 nanostructures. The effect of process parameters on their morphology is investigated. The structure is verified through SEM, EDX, XRD. Uniform and smoother nanofibers having a large surface area are fabricated and improved surface area is verified through BET. Potential applications are catalysis, medical, energy‐conservation and environmental protection.